2014
DOI: 10.3109/13880209.2014.936944
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis andin vitroantiviral and antifungal activities of essential oils fromGlechon spathulataandGlechon marifolia

Abstract: The chemical composition for G. spathulata and G. marifolia essential oils is very similar. The oil of G. spathulata can be promising as a new antifungal agent against dermatophytes. The findings add important information to the biological activity of Glechon species essential oils, specifically its antiviral and antidermatophytic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
3
29
0
2
Order By: Relevance
“…The essential oil of M. insularis showed the highest activity against Staphylococcus xylosus with an MIC value of 3.6  μ L/mL. Moreover, Venturi et al [82] reported the antifungal action of the essential oils extracted from Glechon spathulata and G. marifolia against the dermatophytic fungi Trichophyton rubrum and Epidermophyton floccosum . The MIC values ranged from 10 to 83 mg/mL against T. rubrum and 83 to 500 mg/mL against E. floccosum .…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of M. insularis showed the highest activity against Staphylococcus xylosus with an MIC value of 3.6  μ L/mL. Moreover, Venturi et al [82] reported the antifungal action of the essential oils extracted from Glechon spathulata and G. marifolia against the dermatophytic fungi Trichophyton rubrum and Epidermophyton floccosum . The MIC values ranged from 10 to 83 mg/mL against T. rubrum and 83 to 500 mg/mL against E. floccosum .…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…HSV-1 is the cause of common viral infections in humans, such as herpetic keratitis, herpetic encephalitis, mucocutaneous herpes infections, and neonatal herpes. Studies on the essential oils of Artemisia arborescens, Glechon spathulata , and Glechon marifolia found that they strongly suppressed HSV-1 [82, 93, 138]. Melissa officinalis essential oils have major constituents, namely, citral and citronellal, which could inhibit the replication of HSV-2 [96, 133, 137].…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Moreover, some EOs have been used in cancer treatment (6)(7)(8), while others are used in food preservation, fragrance, and aromatherapy industries. EOs are valuable sources of biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These observations show that the significant activity of M. exotica leaf may be due to the presence of major chemical constituents such as β-caryophyllene. Several studies reported that β-caryophyllene in other plants possessed insecticidal activity (Zhu & Tian, 2011;Krishnamoorthy et al, 2015;Venturi et al, 2015;Salleh et al, 2015). M. exotica as a popular hedge plant well adapted for topiary work is widely distributed in southern China and several tropical and subtropical regions of Asia.…”
Section: Discussionmentioning
confidence: 99%